Halal Tourism Business Development with Information Technology Development - Sugiarto; Mohammad Idhom (Future Science)
Institute of Research and Community Service wherein its development emerged an institution called Business Incubator, where Business Incubator (Inbis) is named Technopark Business Incubator has some activities that support startup that again developed outside the campus as well. From the development of this Startup also the Ministry of Research, Higher Education also has a program or scheme for Business Incubator of each Institution both private and State to bias develop innovation and application of technology in related fields. So Inbis Technopark also has a program for lecturers at UPN